Development of a Workplace Well-being Scale in the Context of Islamic Boarding Schools (Pesantren) - Aryani Pamukti; Fathul Lubabin Nuqul; Retno Mangestuti; Mohammad Mahpur; Elok Halimatus Sa’diyah (Universitas Muhammadiyah Surakarta, 2025)
This research explores workplace well-being in the context of Islamic boarding schools in Indonesia, with a focus on aspects of justice, sincerity, obedience and calling. Workplace well-being in Islamic boarding schools includes a healthy work environment, social support, work-life balance, recognition of contributions, career development, and access to physical and mental health resources. Pesantren as an integral Islamic educational institution in Indonesian Muslim society has a unique approach to workplace well-being, which involves the values of simplicity, sincerity, independence, Islamic brotherhood and independence. This research uses a mixed method which combines qualitative grounded theory and quantitative descriptive approaches. Data was collected through interviews, observation and Likert scales. Development of an Islamic boarding school workplace well-being measuring tool through the steps of developing a theoretical framework, preparing a blueprint, writing items, expert assessment, reading tests, psychological scale tests, differential power and reliability analysis, and preparing the final scale. This measuring instrument was tested using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), showing four factors that were able to explain 90% of the variance in workplace well-being in Islamic boarding schools. CFA results indicate high validity and reliability of this instrument. Workplace well-being in Islamic boarding schools is formed from justice, sincerity, obedience and calling, which emphasizes internal spirit over external needs, approaching workplace spirituality from a positive psychology perspective. This research concludes that workplace well-being in Islamic boarding schools can be achieved through a harmonious balance between justice, obedience, sincerity and calling in carrying out Islamic boarding school duties.